Fasted to fed trafficking of Fatty acids in human adipose tissue reveals a novel regulatory step for enhanced fat storage. - Ruge, T; Hodson, L; Cheeseman, J; Dennis, A; Fielding, B; Humphreys, S; Frayn, K; Karpe, F (2009)
CONTEXT: Absence or excess of adipose tissue are both associated with metabolic complications, implying the importance of well-functioning adipose tissue present in normal amounts. Adipose tissue sequesters dietary fat and thus protects other tissues from excess fat exposure, especially after meals. OBJECTIVE: The objective of the study was the use of an integrative physiological technique to quantify trafficking of fatty acids (FAs) in adipose tissue over a 24 h period. METHODS: Adipose tissue FA handling was studied in response to three meals in eight healthy men by the combination of arteriovenous blood sampling, tissue blood flow, and specific labeling of FA tracing of exogenous and endogenous fat by stable isotope methodology. RESULTS: The efficiency of adipose tissue FA uptake increased robustly with each meal. Chylomicron-triglyceride was the dominating source of FA. Adipose tissue fractional extraction of chylomicron-triglyceride increased from 21 +/- 4 to 47 +/- 8% (P = 0.03) between the first and last meal. Although adipose tissue lipoprotein lipase action increased with time (2-fold), there was an even greater increase in FA reesterification (3-fold), which led to a reduced spillover of chylomicron-derived FA, from 77 +/- 15 to 34 +/- 7% (P = 0.04) comparing the end of the first and the third meal period. Increased uptake of very low-density lipoprotein-derived FA was observed, but spillover of very low-density lipoprotein-derived FA was seen only in the fasting state. CONCLUSION: Human adipose tissue has a significant potential to up-regulate fat storage during a normal day that goes beyond increased lipoprotein lipase activation. The adaptation toward increasing fat storage may provide an explanation for the beneficial properties of normal amounts of adipose tissue.